Dynamics Model of 4-PRP+3-UPS&PU Hybrid Machine Tool with Redundant Drive - Liu Na; Mei Ying; Wang Shusen; Hu Weiwei (Jixie chuandong)
The Lagrange method is applied to build dynamics model of the 6 DOF redundantly actuated hybrid machine tool. Firstly,the configuration of the 4-PRP + 3-UPS&PU machine tool is analyzed,and the coordinate system is established. Then,the expression of kinetic energy and potential energy of the machine tool are educed,and the equivalent generalized force of non-conservative force is analyzed,and the dynamics model is established by using the Lagrange method,which laid the foundation for the solution of driving force and dynamics analysis. Finally,combining with numerical examples,the numerical results of the dynamics model of the 4-PRP + 3-UPS&PU redundant drive hybrid mechanism and mechanism driving rod drive curve are obtained by MATLAB,and the correctness and feasibility of the dynamic model is verified by ADAMS simulation results.